(untitled) (CIPEEX, 2025)
The relationship between work and health in general is complex and requires attention to the core executive functions of teachers. Excessive demands can cause cognitive sequelae, directly affecting quality of life. Thus, it is essential to understand these effects in order to promote actions aimed at the well-being of these professionals. The study evaluated the presence of cognitive sequelae and their effects on the quality of life of teachers in the São Patrício Valley. A quantitative cross-sectional study was conducted, approved by the Research Ethics Committee (opinion no. 6,144,987). The study was carried out in the São Patricio Valley and investigated cognitive sequelae and aspects of quality of life in 50 teachers from the federal, state, and municipal public school systems. The instruments used for data collection were the Span of Digits test, related to cognition, and the WHOQOL-100, which covers items related to quality of life. Statistical analysis was performed using Sigma Plot software. Federal school teachers performed better in repetition after interference, while state school teachers excelled in reverse span, suggesting greater efficiency in working memory. Municipal school teachers, on the other hand, scored low on all tasks, indicating impaired information retention and manipulation. In terms of quality of life, teachers in federal, state, and municipal schools reported high scores in the WHOQOL-100 domains when compared to professionals in alternative management initiatives. The findings reinforce the hypothesis that the institutional context and management model can influence both the cognitive health and quality of life of teachers. The findings suggest that teachers’ cognitive performance and perception of quality of life vary according to the administrative sphere and institutional model. Teachers in the federal and state school systems demonstrated greater cognitive efficiency, while teachers in the municipal school system performed less well, indicating cognitive weaknesses in the work context. In addition, perceived quality of life was satisfactory among teachers in traditional networks compared to those linked to other management models. Therefore, institutional and organizational factors can be considered elements that directly influence both the cognitive health and general well-being of professionals.